Madrasah dan Ujian Nasional - Supa’at, Supa’at (FITK UIN Walisongo, 2013)
This research analysis the implication of the policy of the national final exams (Ujian Nasional-UN) in basic to high school that conducts every year by the government, the ministry of education and culture. This researchnot discussabout the validity of UN as government policy, butthe main focus of this research is the implication of UN to madrasah as Islamic education ins-titution that has unique and different character from general school. AsIslamic education,curriculum of madrasah based on the Islamic teachings which the sublime behavior as the final objective of Islamic education. In reality, the policy of UN has caused madrasah to become trapped in practical efforts to help student pass by focusing on repetitive practice of test inexamination subject.The defication of test scores and the application of the policy standardization have result in the process education causing fear in students, teachers, and madrasah management. Finaly, students experientstress and depressiondue to fear of failing the UN. Â AbstrakPenelitian ini mengkaji implikasi dari kebijakan Ujian Nasional (UN) mulai dari Sekolah Dasar sampai Sekolah Menengah Atas yang dilakukan setiap tahun oleh Pemerintah, Kementrian Pendidikan dan Kebudayaan. Penelitian ini tidak membahas tentang keabsahan UN sebagai kebijakan pemerintah, tetapi fokus utama dari penelitian ini adalah implikasi dari UN untuk madrasah sebagai institusi pendidikan Islam yang memiliki Karakter yang unik dan berbeda dari sekolahumum. Sebagai pendidikan Islam, kurikulum madrasah didasarkan ajaran Islam yang luhur perilaku sebagai tujuan akhir pendidikan Islam. Pada kenyataannya,kebijakan UN telah menyebabkan madrasah menjadi terjebak dalam upaya praktis untuk membantu siswa lulus dengan berfokus pada praktek berulang tes dalam subjek pemeriksaan. Perolehan nilai ujian dan penerapan standarisasi kebijakan mengakibatkan rasa takut pada siswa, guru, dan manajemen madrasah. Akhirnya, siswa mendapati stres dan depresi karena takut gagal dalam UN.